(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2020)
Poetry writing, as one of learning activities which is thought by teacher, need to be re-evaluated. The traditional learning method that limits students creativity must be removed. This research aims to upgrade the poetry writing skill through outdoor study method that takes a month of period. The researcher uses Classroom Action Research (CAR) and processes the data quantitatively. The result of the research shows that the poetry writing skill of students increase as time goes by. It can be seen from the first cycle that has 74.39% to be 86.25% in the second cycle. As well as the students writing skill, it also increases the result of teacher and student activity that is observed. The percentage of teacher activity increases from 86.60 % in the first cycle to be 93.75 % in the second cycle, meanwhile the student activity increases from 84.08 % in the first cycle to be 89.28 % in the second cycle. From these results, it can be concluded that outdoor study as the method of learning, increases students writing skill especially for poetry writing.